Differences In Communication And Problem Solving Skills Teaching With A Constructivism Approach And Realistic Mathematics Education - Uzdah, Nafilah (Mahir : Jurnal Ilmu Pendidikan dan Pembelajaran, 2022)
This study aims to determine the differences in students' mathematical communication and problem solving abilities who are taught using a constructivism learning approach and realistic mathematics education (PMR) on the subject matter of geometry transformation for class XII MIA Al-Wasliyah 12 association. This study uses quantitative research methods, with type of quasi-experimental research. The population is all class XII MIA MA Al-Wasliyah 12 Perbaungan for the 2020/2021 academic year. The samples used were XII MIA I and XII MIA II, each of which amounted to 35 students. The sampling technique used was total sampling technique. Data was collected using the instrument of communication skills and students' mathematical problem solving. Data analysis was performed using two-way analysis of variance (ANOVA). These findings show: There are differences in the mathematical communication skills of students who are taught using constructivism learning approaches and realistic mathematics education (PMR) with Fcount = 4.226 and Ftable at the level (???? = 0.05) = 3.98. There is a difference in the mathematical problem solving ability of students who are taught using a constructivism learning approach and realistic mathematics education (PMR) with Fcount = 7.646 and Ftable at the level (???? = 0.05) = 3.98. ABSTRACT   This study aims to determine the differences in students' mathematical communication and problem solving abilities who are taught using a constructivism learning approach and realistic mathematics education (PMR) on the subject matter of geometry transformation for class XII MIA Al-Wasliyah 12 association. This study uses quantitative research methods, with type of quasi-experimental research. The population is all class XII MIA MA Al-Wasliyah 12 Perbaungan for the 2020/2021 academic year. The samples used were XII MIA I and XII MIA II, each of which amounted to 35 students. The sampling technique used was total sampling technique. Data was collected using the instrument of communication skills and students' mathematical problem solving. Data analysis was performed using two-way analysis of variance (ANOVA). These findings show: There are differences in the mathematical communication skills of students who are taught using constructivism learning approaches and realistic mathematics education (PMR) with Fcount = 4.226 and Ftable at the level (???? = 0.05) = 3.98. There is a difference in the mathematical problem solving ability of students who are taught using a constructivism learning approach and realistic mathematics education (PMR) with Fcount = 7.646 and Ftable at the level (???? = 0.05) = 3.98.